A Honeycomb-Shaped Brass Plate Catalyst to Reduce Motor Vehicle Emissions - Ali Mokhtar; Ali Saifullah; Andinusa Rahmandhika (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
The increasing number of motorized vehicles has a direct impact on exhaust gas air pollution. The air pollution in urban areas is dominated by motorized vehicle emissions, along with pollution problems. This study aims to reduce motor vehicle emissions by using a catalytic converter design made from a brass plate catalyst in the shape of a honeycomb. Honeycomb-shaped brass is suitable for catalysts in the catalytic converter. Besides being easy to obtain and cheap in price, the catalyst can reduce and oxidize exhaust gases well, making it suitable as a catalyst material. The method used in this research is the experimental method. It is started from the design of the catalytic converter house and determining the type of catalyst to the process of making the catalytic converter with a honeycomb-shaped brass plate. Then, testing to determine the emission of exhaust gases produced is required. The last step is to compare it without using a catalytic converter or standard conditions. From the results of the emission test, it was found that the use of a catalytic converter made from a brass plate catalyst in the shape of a honeycomb can reduce HC and CO emissions, while CO2 emissions have increased. A decrease in HC gas emissions by 19.1% for a single catalytic converter and 33.7% for a dual catalytic converter is better compared to without using a catalytic converter or standard conditions. Reduced CO gas emissions by 23.8% for a single catalytic converter and 43.1% for a dual catalytic converter are compared to without using a catalytic converter. Meanwhile, CO2 gas emissions increased by 60.7% for a single catalytic converter, and 81.6% for multiple catalytic converters are compared without using a catalytic converter. This is a result of the addition of oxygen to the oxidation process that running smoothly.